Reforming Singapore’s law on division of matrimonial assets - TEO, Jia En (Institutional Knowledge at Singapore Management University, 2022)
Section 46(1) of the Women’s Charter undergirds the sacrosanct institution that is marriage – it lays out its moral basis and expresses society’s hopes and expectations of the ideal marital relationship: marriage is an equal cooperative partnership of different efforts for mutual benefit. It is thus no surprise that even when a marriage is terminated, the division of matrimonial assets is also founded upon this prevailing ideology. However, as opposed to equal division, Singapore law dictates a “just and equitable” division of matrimonial assets, where wide discretion and power is vested in the judiciary. This legal rule has been criticised to be vague and unpredictable, which in turn fuels more litigation and contradicts an equally important principle in family divorce law – harmonious termination of marriage and resolution of disputes with minimum acrimony and distress as far as possible. This article will examine the underlying rationale for the present law on division of matrimonial assets and the problems with the current approach, explore fundamental concepts such as the notion of fairness and the partnership theory of marriage, before concluding with the possible reforms which may be adopted by Singapore’s law on division of matrimonial assets.